2011
DOI: 10.1063/1.3615948
|View full text |Cite
|
Sign up to set email alerts
|

Presence of excited electronic state in CaWO4 crystals provoked by a tetrahedral distortion: An experimental and theoretical investigation

Abstract: By combining experimental techniques such as x-ray diffraction, Fourier transform Raman, ultraviolet-visible, x-ray absorption near edge structure, extended x-ray absorption fine structure spectroscopy, and theoretical models, a general approach to understand the relationship among photoluminescence (PL) emissions and excited electronic states in CaWO 4 crystals is presented. First-principles calculations of model systems point out that the presence of stable electronic excited states (singlet) allow us to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 126 publications
5
80
0
Order By: Relevance
“…This trend is more apparent for Ca (1−1.5x) Eu x WO 4 , which has vacancies in the structure. The positions and shapes of each peak are almost identical with those of Gracia et al 19 and Cavalcante et al 20 In Figure 5, the positions of Figure 5. FT-Raman spectra of CaWO4, Ca0.85Eu0.10WO4, and Ca0.80Eu0.10Na0.10WO4.…”
Section: +supporting
confidence: 80%
“…This trend is more apparent for Ca (1−1.5x) Eu x WO 4 , which has vacancies in the structure. The positions and shapes of each peak are almost identical with those of Gracia et al 19 and Cavalcante et al 20 In Figure 5, the positions of Figure 5. FT-Raman spectra of CaWO4, Ca0.85Eu0.10WO4, and Ca0.80Eu0.10Na0.10WO4.…”
Section: +supporting
confidence: 80%
“…Gracia et al [78] have demonstrated that the CCCT mechanism in CaWO 4 crystals at excited states (excited singlet and excited triplet) can be considered a new class of electronic transitions which are involved in PL emissions. In this work, we consider that within the β-ZnMoO 4 lattice, the octahedral [ Intensity (arb.…”
Section: ()mentioning
confidence: 99%
“…7 Breaking symmetry processes of these clusters such as distortions, breathings, and tilts create a huge number of different structures; this phenomenon can be related to short-, intermediate-and long-range structural order−disorder that subsequently creates different materials properties. Therefore, for a α-Ag 2 WO 4 material, structural and electronic properties can primarily be associated with cluster constituents, and the disparity or mismatch of both clusters can induce structural order−disorder effects that will significantly influence their luminescence and photodegradation processes.…”
Section: Introductionmentioning
confidence: 99%